Versatile human in vitro triple coculture model coincubated with adhered gut microbes reproducibly mimics pro‐inflammatory host‐microbe interactions in the colon. Issue 12 (1st November 2021) - Beterams, Annelore; De Paepe, Kim; Maes, Laure; Wise, India Jane; De Keersmaecker, Herlinde; Rajkovic, Andreja; Laukens, Debby; Van de Wiele, Tom; Calatayud Arroyo, Marta
Abstract: The colonic epithelial barrier is vital to preserve gut and host health by maintaining the immune homeostasis between host and microbes. The mechanisms underlying beneficial or harmful host‐microbe interactions are poorly understood and impossible to study in vivo given the limited accessibility and ethical constraints. Moreover, existing in vitro models lack the required cellular complexity for the routine, yet profound, analysis of the intricate interplay between different types of host and microbial cells. We developed and characterized a broadly applicable, easy‐to‐handle in vitro triple coculture model that combines chemically‐induced macrophage‐like, goblet and epithelial cells covered by a mucus layer, which can be coincubated with complex human‐derived gut microbiota samples for 16 h. Comparison with a standard epithelial monolayer model revealed that triple cocultures produce thicker mucus layers, morphologically organize in a network and upon exposure to human‐derived gut microbiota samples, respond via pro‐inflammatory cytokine production. Both model systems, however, were not suffering from cytotoxic stress or different microbial loads, indicating that the obtained endpoints were caused by the imposed conditions. Addition of the probiotic Lactobacillus rhamnosus GG to assess its immunomodulating capacity in the triple coculture slightly suppressed pro‐inflammatory cytokine responses, based on transcriptomic microarray analyses. TNF conditioning of the models prior to microbial exposure did not cause shifts in cytokines, suggesting a strong epithelial barrier in which TNF did not reach the basolateral side. To conclude, the triple coculture model is tolerable towards manipulations and allows to address mechanistic host‐microbe research questions in a stable in vitro environment.